Investigating the Modal Behavior of a Violin Top and a Back Plate - Akar, Özge; Willner, Kai (Conference Proceedings of the Society for Experimental Mechanics Series, 2022)
Regarding structural dynamic behavior, the violin is a very versatile entity to study, since it combines many different effects in one single structure. Investigating this instrument means dealing with the uncertainty in natural materials, geometric nonlinearities, many interfaces, and sound radiation. Hence, this multifaceted structure serves as research subject for present work. The study starts with modal analyses of the raw spruce and maple woods, with the intention to show that an a priori material parameter identification is possible. The identified values serve as input for the orthotropic violin plates in the associated finite element model. Using 2D laser scanning vibrometry, the modal parameters are obtained for each plate. The components are supported on soft foams and on cotton wool in order to show the significant deviations in the measurement results with varying foam compliances.
CRIS-Team Scopus Importer:2022-08-26
Keywords: FEM; LDV; Modal; Violin